Analisis Pengaruh Gaya Kepemimpinan Partisipatif, Motivasi, Dan Disipilin Kerja Terhadap Kinerja Pegawai Pada PT. Bank Perekonomian Rakyat Syariah Gebu Prima - Amelia NST, Putri; Hasugian, Hotbin; Maidalena, Maidalena (Universitas Hamzanwadi, 2025)
The purpose of this study is to determine how PT. The People's Economic Bank Syariah Gebu Prima employees perform in relation to motivation, work discipline, and participative leadership style. An employee of the PT is the focus of this investigation. Syariah's People's Economic Bank With up to 30 responders, Gebu Prima was outstanding. using a technique for gathering data that involves questionnaires and observation. To get correct data findings for drawing conclusions, the validity and reliability tests, multiple linear regression analysis, partial (t-test) and simultaneous (f-test) hypothesis tests, and determination coefficients (R_2) were employed as tool instruments. Employee performance is positively impacted by leadership style, positively impacted by motivation, and positively impacted by work discipline, according to the study's findings. Consequently, it may be said that work discipline, motivation, and a participative leadership style are